IN VITRO EVALUATION OF CONCENTRATE FEED CONTAINING Indigofera zollingeriana IN GOAT - Suharlina, S.; Astuti, D. A.; Nahrowi, N.; Jayanegara, A.; Abdullah, L. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
This study was conducted to evaluate the fermentability and nutrient digestibility of concentrate feed containing Indigofera zollingeriana using in vitro technique. Randomized complete block design was used on 3 types of concentrate feed and 4 groups (replicates) of goat's rumen liquid. The concentrate feeds were R1, R2 and R3 containing I. zollingeriana at 0 (control), 20 and 40%, respectively. Variables observed were total gas production, in vitro dry matter digestibility (IVDMD), organic matter (IVDOM), and crude protein (IVDCP), volatile fatty acid (VFA) profiles and NH3 concentration. Data were analyzed using analysis of variance (ANOVA). Results showed that there was no significant effect of R3 on IVDMD, IVDOM and IVDCP as compared to R1 and R2. However, there was significant difference (P<0.05) of the parameters between R1 and R2 (P<0.05). There was no significant effect (P<0.05) of different Indigofera levels on total gas production. The partial VFA of each concentrate feeds was not significantly different, but the percentage of acetic acids of concentrates containing I. zollingeriana were higher than those of control (P<0.05). The concentration of rumen NH3 of R2 was lower than R1 and R3 (P<0.05) even though the IVCPD of R2 was higher than R1. It could be concluded that the inclusion of I. zollingeriana as concentrate feed ingredient at 20% maximum level .